Mediation analysis of the alcohol‐postmenopausal breast cancer relationship by sex hormones in the EPIC cohort. Issue 3 (30th April 2019) - Assi, Nada; Rinaldi, Sabina; Viallon, Vivian; Dashti, S. Ghazaleh; Dossus, Laure; Fournier, Agnès; Cervenka, Iris; Kvaskoff, Marina; Turzanski‐Fortner, Renée; Bergmann, Manuela; Boeing, Heiner; Panico, Salvatore; et al.
Abstract : Alcohol consumption is associated with higher risk of breast cancer (BC); however, the biological mechanisms underlying this association are not fully elucidated, particularly the extent to which this relationship is mediated by sex hormone levels. Circulating concentrations of estradiol, testosterone, their free fractions and sex‐hormone binding globulin (SHBG), were examined in 430 incident BC cases and 645 matched controls among alcohol‐consuming postmenopausal women nested within the European Prospective Investigation into Cancer and Nutrition. Mediation analysis was applied to assess whether individual hormone levels mediated the relationship between alcohol intake and BC risk. An alcohol‐related hormonal signature, obtained by partial least square (PLS) regression, was evaluated as a potential mediator. Total (TE), natural direct and natural indirect effects (NIE) were estimated. Alcohol intake was positively associated with overall BC risk and specifically with estrogen receptor‐positive tumors with respectively TE = 1.17(95%CI: 1.01, 1.35) and 1.36(1.08, 1.70) for a 1‐standard deviation (1‐SD) increase of intake. There was no evidence of mediation by sex steroids or SHBG separately except for a weak indirect effect through free estradiol where NIE = 1.03(1.00, 1.06). However, an alcohol‐related hormonal signature negatively associated with SHBG and positively with estradiol and testosterone was associated with BC risk (odds ratio [OR] = 1.25 [1.07, 1.47]) for a 1‐SD higher PLS score, and had a statistically significant NIE accounting for a mediated proportion of 24%. There was limited evidence of mediation of the alcohol‐BC association by individual sex hormones. However, a hormonal signature, reflecting lower levels of SHBG and higher levels of sex steroids, mediated a substantial proportion of the association. Abstract : What's new? Alcohol consumption is associated with an increased risk of breast cancer (BC). However, the mechanisms underlying this association are not yet fully understood. For example, do sex‐hormone levels play a role? In this study, the authors assessed a number of alcohol‐related hormonal signatures. They found that lower levels of sex‐hormone binding globulin (SHBG), combined with higher levels of sex steroids, mediate a substantial proportion of the observed alcohol‐BC association. It is likely that the mechanism involves the interplay of multiple hormones, rather than the action of individual hormones.